2012
DOI: 10.3390/nu4122008
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cell Signaling and Apoptotic Pathways by Luteolin: Cardioprotective Role in Rat Cardiomyocytes Following Ischemia/Reperfusion

Abstract: Myocardial ischemia often results in damaged heart structure and function, which can be restored through ischemia/reperfusion (I/R) in most cases. However, I/R can exacerbate myocardial ischemia reperfusion injury (IRI). Luteolin, a widely distributed flavonoid, a member of a group of naturally occurring polyphenolic compounds found in many fruits, vegetables and medicinal herbs, has been reported to exhibit anti-inflammatory, antioxidant and anti-carcinogenic activities. In recent years, luteolin has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…Presence of hydroxyl moieties and 2-3 carbon double bond are responsible for its several biochemical and pharmacological activities [18,19] like anti-inflammatory, antioxidant [6,[18][19][20][21][22], anticancer [18,22], antimicrobial [19,22], anti-allergic [22], anti-diabetic [19]. These evidence indicated that many biological activities of Luteolin (e.g.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Presence of hydroxyl moieties and 2-3 carbon double bond are responsible for its several biochemical and pharmacological activities [18,19] like anti-inflammatory, antioxidant [6,[18][19][20][21][22], anticancer [18,22], antimicrobial [19,22], anti-allergic [22], anti-diabetic [19]. These evidence indicated that many biological activities of Luteolin (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…Luteolin (3',4',5,7-tetrahydroxyflavone), which is naturally distributed among several plant species such as medicinal plants, vegetables and fruits [18,21,22], is structurally classified under the group of flavones [18][19][20]. Presence of hydroxyl moieties and 2-3 carbon double bond are responsible for its several biochemical and pharmacological activities [18,19] like anti-inflammatory, antioxidant [6,[18][19][20][21][22], anticancer [18,22], antimicrobial [19,22], anti-allergic [22], anti-diabetic [19].…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin is heat stable and losses due to cooking are relatively low (Le Marchand, 2002). Luteolin, possess many beneficial properties including antioxidant (Ashokkumar and Sudhandiran, 2008), anti-inflammatory (Nishitani et al, 2013), cardio protective (Xu et al, 2012), anti-diabetic (Salib et al, 2013) and anti-proliferative (Ashokkumar and Sudhandiran, 2011).…”
Section: Luteolin a Bioflavonoid Inhibits Colorectal Cancer Through mentioning
confidence: 99%
“…Myocardial tissue injury induced by ischemia and hypoxia is a major factor underlying the development of fatal diseases. The main cause of myocardial ischemic injury is myocardial cell apoptosis induced by myocardial hypoxia (5). Furthermore, subsequent reoxygenation may further aggravate the damage (6).…”
Section: Introductionmentioning
confidence: 99%